Evolution of the consumption of lorazepam in a rural environment in the Region of Murcia (2012-2018) - Juan Antonio Cano-Hernández; Pura Ballester; Sandra Sierra-Alarcón; Alejandro Galindo-Tovar (Pharmaceutical Care España, 2022)
Objective: To evaluate the consumption of lorazepam in the Region of Murcia, specifically in the district of Mula, during the period 2012-2018, considering age and sex variables.